HUBUNGAN SUPERVISI AKADEMIK DAN INTENSITAS MENGIKUTI PELATIHAN DENGAN KINERJA GURU SMPN SE-KECAMATAN BERMANI ULU KABUPATEN REJANG LEBONG - Raden Tita Suhartati (UNIVERSITAS BENGKULU, 2015)
The purposes of the research are to find out the relationship between: 1) academic supervision and teacher’s performance, 2) training intensity and teacher’s performance , 3) andcorrelation between both of them. The populations and sampel was all teachers of Public Junior High Shool at Bermani Ulu subdistrict. The result of this research show that there are significant correlation between: 1) academic supervision and teacher’s performance is 0,520, 2) training and teacher’s performance is 0,585, 3) and academic supervision, training intensity on teacher’s performance could be shown by using regress formula Y= 31,528 + 0,405 (X1) + 0,296 (x2). Sothe effective contribution of academic supervision on teacher’s performance 27% whereas training variable on teacher’s performance is 34,2%.Key word: academic supervision, training intensity, teacher’s performance